Cultivating Academic Integrity through Islamic Ethical Foundations in Scholarship - Lalu Agus Murzaki (Academia Open, 2025)
(General Background) Academic writing reflects not only intellectual capacity but also ethical responsibility and moral integrity in knowledge production. (Specific Background) Within Islamic education, ethics such as honesty, transparency, and accountability are regarded as fundamental principles that ensure the sanctity of knowledge. However, in today’s digital era, academic ethics face new challenges due to technological developments, including artificial intelligence, which complicate the identification and prevention of academic misconduct. (Knowledge Gap) Existing approaches often limit the understanding of academic integrity to plagiarism detection, neglecting broader ethical dimensions such as methodological transparency and researchers’ social accountability. (Aims) This study aims to explore the ethical foundations of academic writing in Islamic education and to propose a holistic approach that integrates moral, spiritual, and institutional dimensions of integrity. (Results) Using a descriptive qualitative method through library research, findings reveal that ethical education—embedded within the curriculum, training, and mentoring—is crucial for fostering authentic academic integrity beyond mere rule compliance. (Novelty) The study presents an Islamic ethical perspective as a normative and philosophical framework for shaping scholars of integrity in the digital era. (Implications) Strengthening ethical literacy from early education can cultivate a scholarly culture that upholds honesty, transparency, and accountability, ensuring credible and socially beneficial scientific advancement. Highlights: Academic integrity extends beyond plagiarism to encompass honesty and social responsibility. Islamic ethics provide a strong moral foundation for scholarly conduct. Ethical literacy and education are vital to sustain integrity in the digital age. Keywords: Academic Ethics, Islamic Education, Integrity, Plagiarism, Digital Era